Flupyradifurone effectively manages whitefly Bemisia tabaci MED (Hemiptera: Aleyrodidae) and tomato yellow leaf curl virus in tomato. Issue 8 (19th May 2017) - Roditakis, Emmanouil; Stavrakaki, Marianna; Grispou, Maria; Achimastou, Aikaterini; Van Waetermeulen, Xavier; Nauen, Ralf; Tsagkarakou, Anastasia
Abstract: BACKGROUND: The cotton whitefly Bemisia tabaci (Gennadius) is among the most important pests of numerous crops and a vector of more than 100 plant viruses, causing significant crop losses worldwide. Managing this pest as well as inhibiting the transmission of major viruses such as tomato yellow leaf curl virus (TYLCV) are of utmost importance for sustainable yields. The efficacy against both whitefly and virus transmission of the novel systemic butenolide insecticide flupyradifurone was investigated in this study. RESULTS: The inhibition of TYLCV transmission by flupyradifurone was compared to that by thiamethoxam, a neonicotinoid insecticide reported to inhibit virus transmission. The experiment was performed under high virus pressure conditions (10 viruliferous insects per plant for 48 h) using a fully characterized field strain of B. tabaci . The insecticides were foliarly applied at recommended label rates under greenhouse conditions. Flupyradifurone suppressed virus transmission by 85% while levels of suppression after thiamethoxam treatments were just 25% and significantly lower. In untreated control plots, 100% of plants were infected by TYLCV. The observed difference in the potential to suppress virus transmission is linked to a strong knockdown effect as well as prolonged feeding inhibition in flupyradifurone treatments. CONCLUSION: Flupyradifurone is shown to be an extremely useful, fast‐acting, new chemical tool in integrated crop management offering simultaneous control of whiteflies and strong suppression of viral infections via its rapid knockdown action and good residual activity. © 2017 Society of Chemical Industry